1999
DOI: 10.1086/302195
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Human Obesity and Linkage to Markers in 20q13

Abstract: Obesity is a highly prevalent, multigenic trait that predicts increased morbidity and mortality. Here we report results from a genome scan based on 354 markers in 513 members of 92 nuclear families ascertained through extreme obesity and normal body weight. The average marker interval was approximately 10 cM. We examined four correlated obesity phenotypes, including the body-mass index (BMI) (both as a quantitative trait and as a discrete trait with a threshold of BMI > or /=30 kg/m2) and percentage of fat (bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 88 publications
10
128
2
Order By: Relevance
“…Early reports indicated relatively consistent findings for 10p from three studies of US European American, French, and German cohorts. [19][20][21]63 Subsequently, several other reports on obesity-related phenotypes have found signals in the same or nearby chromosomal regions, but also including signals on 1q, 12 12,27 None of these studies have reported sex-specific linkage findings.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports indicated relatively consistent findings for 10p from three studies of US European American, French, and German cohorts. [19][20][21]63 Subsequently, several other reports on obesity-related phenotypes have found signals in the same or nearby chromosomal regions, but also including signals on 1q, 12 12,27 None of these studies have reported sex-specific linkage findings.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment processes have been described previously. 26,27 After obtaining informed consent, the probands and their biological parents and full siblings were measured for weight, height, waist circumference, percent body fat and other anthropometric measurements. Blood samples were also collected.…”
Section: Familiesmentioning
confidence: 99%
“…Interestingly, PTPN1, the gene coding for PTP-1β, is located in a genomic region that has been identified in numerous linkage studies as a QTL for obesity and diabetes (Ghosh et al 1999;Lee et al 1999;Soro et al 2002). PTP-1β affects plasma lipid levels and might result in obesity and hypertension in Japanese and Chinese populations.…”
Section: Discussionmentioning
confidence: 99%